2016
DOI: 10.15171/jlms.2016.03
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Transurethral Cystolithotripsy of Large Bladder Stones by Holmium Laser

Abstract: Introduction: To assessment of the efficacy and safety of transurethral cystolithotripsy of large bladder stones by holmium laser in the outpatient setting. Methods: In a prospective study, 48 consecutive adult patients with large bladder stones, were enrolled for transurethral cystolithotripsy. Patients older than 18 years, with bladder stones larger than 2 cm were enrolled. Urethral stricture, active urinary infection, and any anesthetic contraindications for operation, were the exclusion criteria. Demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
8
0
3
Order By: Relevance
“…Major complications and recurrence of bladder stone were not seen. 42 Another study was about the safety and efficacy of laser lithotripsy in pregnancy reported by Abedi et al In this retrospective study, 15 pregnant women with ureteral stones treated with semi-rigid ureteroscope and holmium laser were included. They concluded that laser lithotripsy is a safe method in pregnant patients with ureteral stone where conservative treatment failed.…”
Section: Treatment Of Urolithiasis With Lasermentioning
confidence: 99%
“…Major complications and recurrence of bladder stone were not seen. 42 Another study was about the safety and efficacy of laser lithotripsy in pregnancy reported by Abedi et al In this retrospective study, 15 pregnant women with ureteral stones treated with semi-rigid ureteroscope and holmium laser were included. They concluded that laser lithotripsy is a safe method in pregnant patients with ureteral stone where conservative treatment failed.…”
Section: Treatment Of Urolithiasis With Lasermentioning
confidence: 99%
“…Transurethral cystolithotripsy (TUCL) is the choice of current interventions for bladder stones in adults and children [1,2]. Although it has the same e cacy as percutaneous cystolithotripsy (PCCL) and shorter hospital stay than PCCL, complications could occur [1,[3][4][5]. A rare complication of bladder rupture with stone slipping out would be encountered.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent results of outpatient transurethral cystolithotripsy of large bladder stones was presented by Karami et al in 2016. In their study, the mean time of hospital admission of patients was 6.5 h [ 4 ]. In the study by Kara et al describing transurethral cystolithotripsy with a Holmium laser under local anesthesia, the mean hospital stay was 2.3 days [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous index procedures for cystolithiasis, either transurethral or percutaneous; but, open surgery remains the only way to remove the majority of larger stones intact, although it causes the most morbidity. Less morbid endoscopic treatment modalities are afflicted by the potential for incomplete stone clearance [ 4 , 5 ]. The use of shockwave lithotripsy (SWL) provides the minimal morbidity, with up to 90% effectiveness; but, in one-third of the patients, additional procedures are required [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%